Valproate-Induced Weight Gain - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
To determine the relation of carnitine and insulin levels to weight gain during valproate therapy of epilepsy in children, twenty patients were randomly assigned to receive either carnitine or placebo supplementation, in a study at Hacettepe University, Ankara, Turkey.